Quantum Integrable 1D anyonic Models: Construction through Braided Yang-Baxter Equation - Kundu, A. (Symmetry, Integrability and Geometry: Methods and Applications, 2010)
Applying braided Yang-Baxter equation quantum integrable and Bethe ansatz solvable 1D anyonic lattice and field models are constructed. Along with known models we discover novel lattice anyonic and q-anyonic models as well as nonlinear Schrödinger equation (NLS) and the derivative NLS quantum field models involving anyonic operators, N-particle sectors of which yield the well known anyon gases, interacting through δ and derivative δ-function potentials.